Um estudo da educação financeira no Brasil: uma proposta de categorização de elementos do letramento financeiro - Trindade, Lilian Brazile (2023)
This research is a doctorate thesis from the Graduate Studies Program of Mathematics Education from the Exact Sciences and Technology Faculty of São Paulo Catholic University in which financial education is the central theme. The general aim is to identify and categorize the elements of financial literacy arranged in public documents of the Financial Education in Brazil. In the literature review, a mapping of related researches of the proposed theme was carried out, however it was not identified any study within the scope of pertinent elements of financial literacy, nevertheless researches were presented which contributed for the elaboration of this thesis. The theoretical basis of this research was the Ecology of Didacts for the ecosystem study of financial education. The methodology used was a documental research as the analyzed public documents are primary and no kind of analytical treatment was carried out. For this study, content analysis procedures were used from the elements found in the primary public documents of financial education in Brazil. These documents were selected in the light of the identified contexts in the skills of the Mathematics curricular component from the Common Curricular National Base, these contexts were based on the criteria of the definition of School Financial Education. After the analysis, four categories were entitled: Financial Citizenship, Financial Planning, Credits and Investments, which contain the respective elements, which can be measured through the proposal developed in this thesis of the five Levels of Proficiency in Financial Literacy, they are: Recognition, Comprehension, Analysis, Manipulation and Autonomy. And finally, for the citizen to be financially literate, it is necessary to have a set of skills regarding the categories and elements presented